2015
DOI: 10.3310/hta19460
|View full text |Cite
|
Sign up to set email alerts
|

A scoping study to explore the cost-effectiveness of next-generation sequencing compared with traditional genetic testing for the diagnosis of learning disabilities in children

Abstract: BackgroundLearning disability (LD) is a serious and lifelong condition characterised by the impairment of cognitive and adaptive skills. Some cases of LD with unidentified causes may be linked to genetic factors. Next-generation sequencing (NGS) techniques are new approaches to genetic testing that are expected to increase diagnostic yield.ObjectivesThis scoping study focused on the diagnosis of LD in children and the objectives were to describe current pathways that involve the use of genetic testing; collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…The 18 reports of diagnostic tests that were excluded because they did not include a systematic review tended to include primary research which informed the economic model parameters. A total of 35 reports [2458] included a health economic evaluation of at least one diagnostic test and a systematic review, and 22 of these [3758] reported the results of a meta-analysis as part of their systematic review. Additionally, there was a single report of a prognostic test, a study of foetal fibronectin testing to predict pre-term birth [59], that included both an economic evaluation, a systematic review, and a meta-analysis of the accuracy of the prognostic test.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The 18 reports of diagnostic tests that were excluded because they did not include a systematic review tended to include primary research which informed the economic model parameters. A total of 35 reports [2458] included a health economic evaluation of at least one diagnostic test and a systematic review, and 22 of these [3758] reported the results of a meta-analysis as part of their systematic review. Additionally, there was a single report of a prognostic test, a study of foetal fibronectin testing to predict pre-term birth [59], that included both an economic evaluation, a systematic review, and a meta-analysis of the accuracy of the prognostic test.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, such molecular testing for children with developmental problems could be undertaken at an early age before the hallmark features characterising particular disorders have become apparent. These technological advances may eventually prove to be more efficient and cost-effective for diagnosis 112 and the RTT clinical criteria which relate to the evolution of the disorder could become redundant.…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…Despite the substantial reductions in sequencing costs following these developments, there is still little information available on the costs of bioinformatics analysis and clinical interpretation (and on what the costs of sequencing are, if not done at scale), as documented in earlier literature reviews. [11][12][13] It is therefore important to understand what economic evaluation evidence is currently available in the literature on clinical applications of WES and WGS, and where there are gaps in the evidence base.…”
Section: Introductionmentioning
confidence: 99%